Characterization of NCI-H295R Cells as an In Vitro Model of Hyperaldosteronism - Lichtenauer, U. D.; Shapiro, I.; Osswald, A.; Meurer, S.; Kulle, A.; Reincke, M.; Riepe, F.; Beuschlein, F. (Hormone and Metabolic Research, 2013)
In depth analysis of key molecular mechanisms involved in functional autonomy of aldosterone secretion is hampered by the lack of tumor cell lines that reflect functional characteristics of aldosterone producing adenomas. Herein, we describe the characteristics of the adrenocortical carcinoma cell line NCI-H295R and its suitability as a model of hyperaldosteronism in relation to different culture conditions. Steroid profiling revealed that NCI-H295R cells predominantly secrete cortisol, while aldosterone and other steroids are released at much lower concentrations. However, aldosterone output specifically increased in response to different stimuli such as ACTH and angiotensin II, and in particular to potassium in a dose dependent manner. NCI-H295R cells readily formed spheroids under specific culture conditions, a method widely used for the enrichment of progenitor cells. Unexpectedly, spheroid cells excelled with higher aldosterone concentration and higher expression levels of the steroidogenic enzymes StAR, 3βHSD, CYP17, SF-1, and the MC2-receptor. Further investigations revealed that this phenomenon is mainly attributed to epithelial growth factor (EGF) and particularly fibroblast growth factor (FGF), which are both essential ingredients in the spheroid culture medium. Aldosterone release under the combinatory influence of EGF and FGF was not higher than the effect of FGF alone. Spheroid growth per se, therefore, does not ensure an enrichment of less differentiated cell types in this cell line.
Keywords: aldosterone producing cell line; Conn’s syndrome; adrenal tumor